Dynamic assessment of registered sexual offenders: the national practitioner perspective on the use of the ‘Active risk management System’ - Mann, Natalie (Policing and society, 2021)
This paper examines police and national probation service (NPS) practitioners’ experiences of utilising a dynamic risk management tool with registered sexual offenders (RSOs) in the community. The Active Risk Management System (ARMS) was designed as a multi-agency tool providing police with a dynamic tool for use with RSOs and the NPS with a sexual offender specific tool to support their original dynamic risk tool OASys (Offender Assessment System). Based on both quantitative and qualitative research with every police force and every NPS division in England and Wales, this paper highlights that despite a comprehensive adoption of ARMS within policing practice, the theoretical benefits of the ARMS tool have unfortunately not been realised. The resource implications of the tool’s utilisation, the different needs and siloed working practices of the police and NPS as well as a staggered implementation of the tool across both agencies has presented challenges for the practical use of ARMS in both single and joint agency offender management.